Answer

Verified

452.1k+ views

Hint: In this question apply the concept that in equilateral triangle all the sides of equilateral triangle is same and later on apply the distance formula between two points, so use these concepts to reach the solution of the question.

The given vertices of the equilateral triangle is (0, 1), (0, -1) and (x, 0)

Now as we know all that in an equilateral triangle all the sides are equal.

So, let the vertices of the triangle be A, B, C.

Therefore,

A = (0, 1), B = (0, -1), C = (x, 0)

So, according to condition of equilateral triangle we have,

AB = BC = CA

So first calculate the distance AB according to distance formula between two points which is given as

$d = \sqrt {{{\left( {{x_2} - {x_1}} \right)}^2} + {{\left( {{y_2} - {y_1}} \right)}^2}} $

Now let's consider

A = (0, 1) $ \equiv \left( {{x_1},{y_1}} \right)$, B = (0, -1) $ \equiv \left( {{x_2},{y_2}} \right)$, C = (x, 0) $ \equiv \left( {{x_3},{y_3}} \right)$

Therefore AB = $\sqrt {{{\left( {{x_2} - {x_1}} \right)}^2} + {{\left( {{y_2} - {y_1}} \right)}^2}} = \sqrt {{{\left( {0 - 0} \right)}^2} + {{\left( { - 1 - 1} \right)}^2}} = \sqrt {{{\left( { - 2} \right)}^2}} = 2$

Therefore BC = $\sqrt {{{\left( {{x_3} - {x_2}} \right)}^2} + {{\left( {{y_3} - {y_2}} \right)}^2}} = \sqrt {{{\left( {x - 0} \right)}^2} + {{\left( {0 - \left( { - 1} \right)} \right)}^2}} = \sqrt {{x^2} + {{\left( 1 \right)}^2}} = \sqrt {{x^2} + 1} $

Therefore CA = $\sqrt {{{\left( {{x_3} - {x_1}} \right)}^2} + {{\left( {{y_3} - {y_1}} \right)}^2}} = \sqrt {{{\left( {x - 0} \right)}^2} + {{\left( {0 - 1} \right)}^2}} = \sqrt {{x^2} + {{\left( { - 1} \right)}^2}} = \sqrt {{x^2} + 1} $

Now as we know all the sides are equal therefore

AB = BC = CA

$ \Rightarrow 2 = \sqrt {{x^2} + 1} $

Now squaring both sides we have,

$

\Rightarrow {2^2} = {x^2} + 1 \\

\Rightarrow 4 - 1 = {x^2} \\

\Rightarrow {x^2} = 3 \\

$

Now take square root we have,

$ \Rightarrow x = \pm \sqrt 3 $

$ \Rightarrow x = \sqrt 3 , - \sqrt 3 $

So, the required value of x is $\sqrt 3 , - \sqrt 3 $.

Hence, option (b) is correct.

Note: In such types of questions the key concept we have to remember is that always recall the distance formula between two points which is stated above then we all know that all the sides of the equilateral triangle is equal, so calculate the distances and equate them as above and simplify, we will get the required value of x, which is the required answer.

The given vertices of the equilateral triangle is (0, 1), (0, -1) and (x, 0)

Now as we know all that in an equilateral triangle all the sides are equal.

So, let the vertices of the triangle be A, B, C.

Therefore,

A = (0, 1), B = (0, -1), C = (x, 0)

So, according to condition of equilateral triangle we have,

AB = BC = CA

So first calculate the distance AB according to distance formula between two points which is given as

$d = \sqrt {{{\left( {{x_2} - {x_1}} \right)}^2} + {{\left( {{y_2} - {y_1}} \right)}^2}} $

Now let's consider

A = (0, 1) $ \equiv \left( {{x_1},{y_1}} \right)$, B = (0, -1) $ \equiv \left( {{x_2},{y_2}} \right)$, C = (x, 0) $ \equiv \left( {{x_3},{y_3}} \right)$

Therefore AB = $\sqrt {{{\left( {{x_2} - {x_1}} \right)}^2} + {{\left( {{y_2} - {y_1}} \right)}^2}} = \sqrt {{{\left( {0 - 0} \right)}^2} + {{\left( { - 1 - 1} \right)}^2}} = \sqrt {{{\left( { - 2} \right)}^2}} = 2$

Therefore BC = $\sqrt {{{\left( {{x_3} - {x_2}} \right)}^2} + {{\left( {{y_3} - {y_2}} \right)}^2}} = \sqrt {{{\left( {x - 0} \right)}^2} + {{\left( {0 - \left( { - 1} \right)} \right)}^2}} = \sqrt {{x^2} + {{\left( 1 \right)}^2}} = \sqrt {{x^2} + 1} $

Therefore CA = $\sqrt {{{\left( {{x_3} - {x_1}} \right)}^2} + {{\left( {{y_3} - {y_1}} \right)}^2}} = \sqrt {{{\left( {x - 0} \right)}^2} + {{\left( {0 - 1} \right)}^2}} = \sqrt {{x^2} + {{\left( { - 1} \right)}^2}} = \sqrt {{x^2} + 1} $

Now as we know all the sides are equal therefore

AB = BC = CA

$ \Rightarrow 2 = \sqrt {{x^2} + 1} $

Now squaring both sides we have,

$

\Rightarrow {2^2} = {x^2} + 1 \\

\Rightarrow 4 - 1 = {x^2} \\

\Rightarrow {x^2} = 3 \\

$

Now take square root we have,

$ \Rightarrow x = \pm \sqrt 3 $

$ \Rightarrow x = \sqrt 3 , - \sqrt 3 $

So, the required value of x is $\sqrt 3 , - \sqrt 3 $.

Hence, option (b) is correct.

Note: In such types of questions the key concept we have to remember is that always recall the distance formula between two points which is stated above then we all know that all the sides of the equilateral triangle is equal, so calculate the distances and equate them as above and simplify, we will get the required value of x, which is the required answer.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Why Are Noble Gases NonReactive class 11 chemistry CBSE

Let X and Y be the sets of all positive divisors of class 11 maths CBSE

Let x and y be 2 real numbers which satisfy the equations class 11 maths CBSE

Let x 4log 2sqrt 9k 1 + 7 and y dfrac132log 2sqrt5 class 11 maths CBSE

Let x22ax+b20 and x22bx+a20 be two equations Then the class 11 maths CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

Give 10 examples for herbs , shrubs , climbers , creepers

Change the following sentences into negative and interrogative class 10 english CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Fill the blanks with proper collective nouns 1 A of class 10 english CBSE